The Influence Of Capital Structure And Macroeconomic Factors On The Profitability Of The Manufacturing Industry In The Consumer Goods (The Indonesian Journal of Business Administration, 2021)
The goal of this research is to look into and analyze the impact of capital structure and macroeconomic factors on profitability in the consumer goods manufacturing industry, which was listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. Return on Equity (ROE), Debt to Equity Ratio (DER), inflation, interest rate, and exchange rate are the research variables. Purposive sampling was used in this study, and a total of 33 companies were sampled. Panel data regression analysis was used as the research method, and EViews 9 was used to process the data. The overall variable has a 6,36 percent effect, according to the findings of this study. Depreciation and amortization (DER), inflation, interest rate, and exchange rates are all variables that have an impact on Return on Equity (ROE).Keywords: Capital Structure, Profitability, Debt to Equity Ratio, Macroeconomic Factor